2022
DOI: 10.1088/1755-1315/962/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Acanthodiaptomus tibetanus (Daday, 1908) (Calanoida, Diaptomidae) – a biogeographic relict in the water bodies of Baikal Rift Zone

Abstract: A detailed morphological description of the copepod Acanthodiaptomus tibetanus and its geographic distribution on the territory of Irkutsk Region, Buryat Republic, Zabaikalsky Region and Republic of Sakha (Yakutia) within the limits of Baikal Rift Zone is presented for the first time. The authors provided information on the paleogeographic conditions of the territory these crustaceans inhabited and characterized their habitats in brief. An overview of the personal data and available literature on the geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Among Calanoida, our research has confirmed the plateau habitation of the relict species Acanthodiaptomus tibetanus (Daday, 1907) [16], which was previously called into question [28]. The finds of two new to science species of the Diaptomidae family deserve special attention.…”
Section: New Records For the Regionsupporting
confidence: 61%
See 1 more Smart Citation
“…Among Calanoida, our research has confirmed the plateau habitation of the relict species Acanthodiaptomus tibetanus (Daday, 1907) [16], which was previously called into question [28]. The finds of two new to science species of the Diaptomidae family deserve special attention.…”
Section: New Records For the Regionsupporting
confidence: 61%
“…Copepodite stages of Cyclopoida and Calanoida were counted separately but only to the genus level without species identification. An Olympus CX-41 highpower microscope was used for accurate crustacean identification following both standard taxonomic treatises and recent taxonomic revisions: [23][24][25][26][27][28] for Copepoda; [29][30][31][32] for Cladocera; and 23 for Anostraca.…”
Section: Samplingmentioning
confidence: 99%